2007
DOI: 10.1080/10837450701212826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cations and Anions on Glass Transition Temperatures in Excipient Solutions

Abstract: The purpose of this study was to investigate the effects of cations and anions of various electrolytes on the glass transition temperature (Tg') of frozen solutions of excipients commonly used in freeze-drying. The effect of electrolyte concentration on freezable water content was also investigated by measuring the enthalpy of melting (DeltaH) using Differential Scanning Calorimetry (DSC). Cations and anions induce changes in Tg' of frozen solutions of commonly used parenteral excipients. These changes are dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The thermal event taking place at − 35 °C, detected for our 10% sucrose solution, may instead be related to the onset of ice dissolution as suggested by Ablett et al 37 A step change could not be observed for the other polymers, which can be explained by the fact that cellulose‐based polymers are strong glass formers, hence having a too small change in heat capacity over the glass transition to be detectable by DSC 39, 40. The addition of the salt was found to decrease the T g ′ of Ficoll by about 9 °C, an effect of that the presence of NaCl increases the amount of water withheld in the freeze concentrate during ice formation 41, 42. In the case of HEC and HPMC an endothermic peak with an onset of − 28 °C and − 27 °C, respectively, appeared when NaCl was included in the formulations, interpreted as the onset of a eutectic melting of NaCl and ice (see Discussion).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The thermal event taking place at − 35 °C, detected for our 10% sucrose solution, may instead be related to the onset of ice dissolution as suggested by Ablett et al 37 A step change could not be observed for the other polymers, which can be explained by the fact that cellulose‐based polymers are strong glass formers, hence having a too small change in heat capacity over the glass transition to be detectable by DSC 39, 40. The addition of the salt was found to decrease the T g ′ of Ficoll by about 9 °C, an effect of that the presence of NaCl increases the amount of water withheld in the freeze concentrate during ice formation 41, 42. In the case of HEC and HPMC an endothermic peak with an onset of − 28 °C and − 27 °C, respectively, appeared when NaCl was included in the formulations, interpreted as the onset of a eutectic melting of NaCl and ice (see Discussion).…”
Section: Resultsmentioning
confidence: 97%
“…A prerequisite for the eutectic melting behaviour is that the components (NaCl and water) are phase separated in the frozen state. NaCl is known to form complexes with the hydroxyl groups of carbohydrates 41, 53. The NaCl to hydroxyl molar ratio in the dry formulations was 1:11, 1:6 and 1:1 for the Ficoll‐, PVA‐ and HEC‐based formulations, respectively, explaining why no or a smaller fraction of crystallised NaCl was detected in the Ficoll and PVA samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…90 Additionally, the presence of salts decreases the T g ' even further. 60,112 On the other hand, a special mechanism where the water behaves like an antiplasticizing agent is also known. 113…”
Section: ■ Discussionmentioning
confidence: 99%
“…No crystalline material was detected in the Ficoll based formulation. NaCl can form complexes with the hydroxyl moieties in carbohydrates 9,10 . In Ficoll and HEC-based formulations the NaCl to hydroxyl moiety molar ratio was 1:11 and 1:1, respectively, explaining why no crystallization was detected in the Ficoll-based formulation.…”
Section: Discussionmentioning
confidence: 99%